2009
DOI: 10.1021/ja904334s
|View full text |Cite
|
Sign up to set email alerts
|

Why Structurally Different Cyclic Peptides Can Be Glycomimetics of the HNK-1 Carbohydrate Antigen

Abstract: The cyclic peptides c-(LSETTl) and c-(RTLPFS) are of potential clinical interest--they stimulate neurite outgrowth in a way that is similar to the effects of the HNK-1 (human natural killer cell-1) antigenic carbohydrate chains, which are terminated by 3'-sulfated glucuronic acid attached to an N-acetyllactosamine unit. To investigate the structure-activity relationships of the ability of the cyclic peptides to mimic HNK-1 carbohydrates, conformational analysis and examination of hydrophobic and hydrophilic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…In the case of JAA-F11, the 3D model can be further employed to guide the rational design of peptide mimotopes of the carbohydrate, for use as immunogens[30], [31], [32], [33], as well as to guide the selection of key residues to be included during antibody humanization. Humanization of a mouse mAb by insertion of the CDRs into a human antibody scaffold, can lead to changes in the 3D conformation, particularly in the interface between the variable light and heavy chains[34], with a corresponding loss of affinity or specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of JAA-F11, the 3D model can be further employed to guide the rational design of peptide mimotopes of the carbohydrate, for use as immunogens[30], [31], [32], [33], as well as to guide the selection of key residues to be included during antibody humanization. Humanization of a mouse mAb by insertion of the CDRs into a human antibody scaffold, can lead to changes in the 3D conformation, particularly in the interface between the variable light and heavy chains[34], with a corresponding loss of affinity or specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Coming back to our design strategy, we hypothesized that the carboxylic functions of the two Glu residues of our peptide might mimic the negatively charged functional groups of the HNK‐1 trisaccharide. However, previously published molecular dynamics (MD) simulations revealed that the distance between the negative groups of HNK‐1 is rather stable, at ∼6 Å . In contrast, distance between the carboxylates of peptide 5 varies between 9.0 and 12.0 Å in our calculated ensemble.…”
Section: Resultsmentioning
confidence: 59%
“…We found that most peptides were recognised by antibodies in saliva to some degree, which provided additional evidence for the selection of biologically-relevant mimotopes, although their amino acid sequences differed. This is not too surprising as several glycomimetic cyclic peptides can exhibit similar physico-chemical properties to their surrogate carbohydrate molecule [14]. …”
Section: Discussionmentioning
confidence: 99%